Efektivitas Permainan Melipat Kertas dan Puzzle terhadap Perkembangan Motorik Halus Anak - Dia Rahmatillah; Ainul Yaqin Salam; Nafolion Nur Rahmat (Jurnal Ventilator, 2023)
Fine motor development is a movement that uses fine muscles or parts of certain limbs that are influenced by opportunities to learn and practice. This study aims to analyse the effectiveness of folding paper and puzzle games on children's fine motor development. The study's research design was a pre-experimental type one-group pretest-posttest design. The population of this study were all children aged 4-5 years at PAUD Ceria Panji Lor Village in September 2023, as many as 28 people with the Total Sampling technique—data collection using DDST Denver II measurement. Analytical test used with Wilcoxon Test. The results showed that children's fine motor development before therapy mainly developed as expected, namely 15 children (54%); after treatment, most developed very well, namely 19 children (68%). This study shows an influence between the value before and after being given folding paper and puzzle game therapy on the fine motor development of children aged 4-5 years.